2019
DOI: 10.3390/ijms20061439
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fermented Oyster Extract against RANKL-Induced Osteoclastogenesis through Scavenging ROS Generation in RAW 264.7 Cells

Abstract: Excessive bone resorption by osteoclasts causes bone loss-related diseases and reactive oxygen species (ROS) act as second messengers in intercellular signaling pathways during osteoclast differentiation. In this study, we explored the protective effects of fermented oyster extract (FO) against receptor activator of nuclear factor-κB (NF-κB) ligand (RANKL)-induced osteoclast differentiation in murine monocyte/macrophage RAW 264.7 cells. Our results showed that FO markedly inhibited RANKL-induced activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Numerous studies have demonstrated that GABA-enriched functional food have physiological benefits such as suppression of blood pressure [ 22 ], hepatoprotection [ 23 ], decrease in gut inflammation [ 24 ], and regulation of glucose tolerance [ 25 ]. Furthermore, several reports have demonstrated that GABA promoted bone health [ 15 , 16 , 26 , 27 , 28 ]. Watanabe et al [ 26 ] reported that GABA directly regulates the muscle tone, and Muhammad et al [ 27 ] suggested GABA promotes osteoblastogenesis by stimulation of bone formation genes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have demonstrated that GABA-enriched functional food have physiological benefits such as suppression of blood pressure [ 22 ], hepatoprotection [ 23 ], decrease in gut inflammation [ 24 ], and regulation of glucose tolerance [ 25 ]. Furthermore, several reports have demonstrated that GABA promoted bone health [ 15 , 16 , 26 , 27 , 28 ]. Watanabe et al [ 26 ] reported that GABA directly regulates the muscle tone, and Muhammad et al [ 27 ] suggested GABA promotes osteoblastogenesis by stimulation of bone formation genes.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al [ 26 ] reported that GABA directly regulates the muscle tone, and Muhammad et al [ 27 ] suggested GABA promotes osteoblastogenesis by stimulation of bone formation genes. More recently, Jeong et al [ 15 ] found that GABA-enriched seaweed suppressed osteoclastogenesis. Additionally, one study reported that peripheral GABA increases plasma GH concentration in humans [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations